EKSISTENSI BI'AH LUGHAWIYAH DI DAYAH TERPADU AL-MUSLIMUN LHOKSUKON ACEH UTARA - Mohd. Nasir Mukhlis, Meutia Rahmah (UIN Sumatera Utara Medan, 2016)
Environment has important role in obtaining language, although in natural or un natural environment. Learning foreign language, needed to form unnatural environment, so the student easy to learn it well. Boarding school is a place to create the unnatural environment, is one of integrated boarding in Aceh which apply